Herpes zoster: A clinical study in 205 patients - E N Abdul Latheef; K Pavithran (Wolters Kluwer Medknow Publications, 2011)
Background: Even though herpes zoster is a common condition its incidence and pattern of occurrence in the era of HIV disease is significant. Aim: To analyze the incidence, pattern of occurrence and evolution of herpes zoster with special attention to provocative factors if any. Materials and Method s: This was an analytical study conducted for 2 years based on a preformed proforma containing preliminary information, a detailed clinical evaluation regarding the segment of involvement, morphology, pattern of lesions, complications, disseminations etc. and investigations to establish provocative factors if any. Results: Incidence of herpes zoster was mainly in the fourth and third decades of life. A definite history of chicken pox was present in only 63.4% cases. In the majority (70%) herpes zoster occurred spontaneously. In 30% cases, immunosuppression due to chemotherapy, malignancy, HIV infection, diabetes mellitus were observed. The commonest segment affected was thoracic (42.4%) followed by cranial (28.2%) and cervical (12.1%). Majority resolved in 7-14 days except immunosuppressed. 34.6% of the patients had complications such as secondary bacterial infection, post herpetic neuralgia, and motor weakness. Ten patients had HIV infection as a provocative factor. Conclusion: The results of incidence and clinical pattern of herpes zoster is almost parallel to the previous studies. Any factors of immunosuppression should be checked, especially HIV, particularly in disseminated and long-lasting cases.